Doses de potássio no crescimento de plantas de mandioca e qualidade de manivas sementes - Silva, Deyse Cristina Oliveira da (2014)
The objective of the present study to evaluate the effect of doses of potassium on plant growth of cassava and quality and quality of the seed stalks grow Aciolina. Three experiments were conducted under field conditions. For the first experiment used a randomized block design in the subdivided plot design, with four replications. The plots were randomized, five doses of potassium (0, 30, 60, 120 and 240 kg ha-1 K2O) and subplots and four times of assessment (150, 210, 270 and 360 days after planting - DAP). The variables evaluated were: leaf area, stem diameter, height of the first branch, number of branches of the first branch, plant height, width of the sheet, length of the petiole of the leaf, number of lobes of the sheet, length and width of the central lobe of the sheet, relationship between the length of the central lobe width of the central lobe, and relationship between petiole length by the length of the central lobe. In the second experiment used randomized blocks, factorial (5x3) design, with five levels of potassium (0, 30, 60, 120 and 240 kg ha-1 K2O) and three plant sections for asexual propagation, with four replications, were evaluated: fresh mass of sections per plant, diameter of sections and number of cuttings per plant. With cuttings obtained from the second experiment, we performed the third experiment adopting the randomized block design with three replications and 15 treatments, consisting of five levels of potassium (0, 30, 60, 120 and 240 kg ha-1 K2O) and three sections of shoots (Foot, 1st Division and 2nd Division). The variables evaluated were: number of shoots for maniva, percentage of shoots of cuttings, plant height, stem diameter, number of leaves, leaf width, petiole length, length and width of the central lobe. The potassium influence of linear and positive way, the growth of cassava plants “cv. Aciolina”. The sections of the plant significantly influence the qualitative components of cuttings showed better results in section 1.